PENERAPAN SANKSI PIDANA BAGI PELANGGARAN HAK CIPTA PENGGANDAAN DVD GAME TANPA IZIN - Yesi Melawati; Lola Yustrisia; Riko Zulfiko (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The development of advanced trade and technology has an impact on the progress of the development of Intellectual Property Rights. Along with these developments, copyright violations are also rife. In this study, the authors wanted to examine the application of criminal sanctions related to copyright infringement, especially the duplication of Digital Versatile Disks with game content. in seeing how the application of criminal sanctions for Copyright violators in duplicating DVD Games, the authors raised the case with decision No. 1766/Pid.B/2014/PN.TNG regarding the duplication of DVD Games without permission by the defendant Anton Sucipto by way of reproducing, copying DVD Game discs using duplicator tools and/or machines located in a rented house in one of the areas in Tangerang City South, Banten. This research is a normative juridical research and is an exploratory research through a statutory approach. The results of the research and discussion conclude that the application of Law No. 28 of 2014 concerning Copyright has been well applied in the study of decisions, but in its application as a deterrent to copyright infringement activities it is still not effective. Copyright infringements will continue to occur due to weak supervision and law enforcement regarding cases such as the duplication of DVD games which are still widely circulated in Indonesia.Keywords: Act of Copyright; DVD Game; Illegal copying